1D AND 2D NMR STUDIES OF 2–(2–(BENZYLOXY)–3–METHOXYPHENYL)–1H–BENZIMIDAZOLE - Mohammed Hadi Al–Douh; Shafida Abd Hamid; Hasnah Osman (Universitas Gadjah Mada, 2007)
The reaction of Benzyl o-vanillin 1 and o-phenylene diamine 2 in dichloromethane produced new benzimidazole, 3. The complete assignments of 3 were made using 1D and 2D NMR including COSY, HMQC and HMBC NMR in CDCl3 and acetone-d6. The coupling constants J are reported in Hertz, and the differences in the peak splittings using both solvents are discussed.